The educational training of children in Late Antiquity: John Chrysostom and the defense of the monastic school - Silva, Gilvan Ventura da (Romanitas - Revista de Estudos Grecolatinos, 2020)
In this article, we intend to examine the John Chrysostom’s ideas regarding the educational formation of children between 380 and 386, when he was a deacon of the Antiochene congregation, after living for six years in the company of the monks who dwelled on the Mt. Silpius. In such occasion he could acquire in loco knowledge about the monastic lifestyle. In order to do that, we analyse the Chrysostom’s arguments exposed in Adversus oppugnatores vitae monasticae, a treatise in which the author not only stands up for the monasticism, but settle the tenets of a Christian pedagogy according to which the parents should let the formation of their children in the monks’ hands instead of sending them to the school of the rhetors and grammarians, whereas the monks were the only ones capable of converting children into honourable men. Eventually, the Chrysostom’s ideas reveal a struggle against the classical school, whose curriculum was based on rhetoric and oratory, pivots of the paideia, but considered useless by him.
Keywords: Late Antiquity; John Chrysostom; Childhood; Christian education; Monasticism